Market reaction to anticipated announcements - Kim, O (Journal of Financial Economics, 1991)
In this paper we analyze how anticipating a forthcoming public announcement affects the market reaction to the announcement by altering investors' incentives to acquire private information. Specifically, we study price change, volume, and information asymmetry at the time of the announcement. We also investigate how information acquisition, information asymmetry, price, and volume are influenced by the quality of prior knowledge, the marginal cost of gathering information, the degree of risk tolerance, and noise. Finally, we compare market reactions to anticipated announcements of known precision with the response to announcements that are either unanticipated or of uncertain quality.